INDONESIAN 2013 CURRICULUM IMPLEMENTATION: TEACHERS’ TECHNIQUES, CHALLENGES, AND VOICES TOWARDS STUDENTS’ AFFECTIVE COMPETENCE - Hanif Nurcholish Adiantika; Dila Charisma; Fitri Aprianti; Eline Rozaliya Winarto (Indonesian EFL Journal, 2021)
One of the prominent alterations in 2013 Curriculum is that this curriculum does not only put an emphasis on cognitive competence but also affective competence. Consequently, the evaluation must be carried out to assess students’ affective assessment. Nevertheless, the issue concerning the complexity of affective assessment has been circulating for years. Therefore, the present study aims to scrutinize teachers’ techniques, challenges, and their voices with regard to development and the implementation of 2013 Curriculum. This study utilizes a qualitative research by using descriptive qualitative design. One teacher, who has implemented 2013 Curriculum, in a senior high school was selected as the respondent in this study. Interviews and document analysis were conducted to obtain the data. This study reveals that there are two evaluation techniques carried out by the teacher specifically observations and peer-assessment. Furthermore, two challenges are identified as teachers’ shortcomings for instance inadequate acquaintance of 2013 Curriculum and time availability in assessment process. Thus, this study recommends teachers to raise their awareness regarding the challenges as well as select an effective technique to assess students’ affective competence. Keywords: Affective assessment; 2013 curriculum; teacher; voice; techniques; challenges